A philosophy of criminal attempts - Donnelly-Lazarov, Bebhinn (Cambridge, UK : Cambridge University Press, 2015)
'An investigation of criminal attempts unearths some of the most fundamental, intriguing and perplexing questions about criminal law and its place in human action. When does attempting begin? What is the relationship between attempting and intending? Do we always attempt the possible and, if so, possible to whom? Does attempting involve action and does action involve attempting? Is my attempt fixed by me or can another perspective reveal what it is? How'much' action is needed for an attempt, how'much' intention is needed and can these matters be decided categorically? Bebhinn Donnelly-Lazarov's answers to these questions will interest criminal law theorists, philosophers and lawyers or law reformers, who encounter the mixed practical and philosophical phenomenon of attempting. Inspired by G. E. M. Anscombe's philosophy, Part I examines attempting generally and its relationship with intention, action subjectivity, and possibility. From the conclusions reached, Part II proposes a specific theory of criminal attempts'--
Machine generated contents note: Part I. The Anatomy of Attempts: 1. Attempts and intention; 2. Attempts and action; 3. Attempts and subjectivity; 4. Attempts and possibility; Part II. Application to Criminal Attempts: 5. Actus reus and mens rea; 6. Impossibility and extraordinariness in criminal attempts; 7. Criminal attempts and moral luck; 8. Reckless attempts?; 9. Inchoate theft and inchoate rape.
Includes bibliographical references and index.
Keywords: Criminal attempt; Criminal intent; Criminal act; Criminal law